The COVID-19 Pandemic and its Medicolegal Aspects in the Indian Context - Purohit , P; Ateriya , A; Setia , P (Journal of Indian Academy of Forensic Medicine, 2023)
Coronavirus disease (COVID-19) is an infectious viral disease caused by a novel coronavirus. The disease has crossed international boundaries and is affecting a large number of people. The present coronavirus outbreak started in China in December 2019 and rapidly spread to other countries. It has involved almost 205 countries around the world and has been declared a pandemic by WHO in March 2020. Human coronaviruses have different strains and these strains cause a severe degree of infection leading to higher mortality in the community. In the time of the recent COVID-19 pandemic, the priority of every healthcare professional was to provide treatment to the affected and suspected person. With no vaccine and insufficient treatment in sight as of now, it is concluded that it is a combined duty of healthcare personnel and citizens across the globe, that correct measures of screening, quarantining, and social distancing are maintained. Healthcare professionals need to be aware of relevant medicolegal issues to avoid future litigations in the court of law. The governments can also work in tandem with the medico-legal experts for improving existing policies and drafting new ones wherever required, so as to be better prepared for any future pandemics.